The Implementation of Cake Applications to Improve Students’ Speaking Skills - Fadila, Amelia Nurul; Aminuddin, Muhammad; Ali, Hapid (Jurnal Perspektif, 2024)
This study aims to find out the students' speaking skills before and after using the Cake Application and the significant difference before and after using the Cake Application on their students' speaking skills. A quantitative method with a pre-experimental design was used in this research. The research was conducted at MAN 1 Karawang which consisted of 25 students as the sample in the tenth-grade class. Pre-test and post-test were part of the six sessions that the research was conducted. The research findings demonstrated that using the Cake Application media significantly improved the students' speaking skills. The pre-test result was 42.24 on average; the maximum score was 68, and the lowest was 32. The average post-test score was 66.72; the top score from the post-test was 100, and the lowest score was 52. In contrast, the speaking scores of the students were higher in the post-test than in the pre-test. In the average N-gain score, it showed that students' speaking skills improved to a medium level of 0,44. Based on research data, using the Cake Application media significantly improved students' speaking skills. The study offers teachers and future researchers as reference materials for using the Cake Applications media in speaking skilss.